Mengukur Dan Mengelola Intellectual Capital - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRACT In the postindustrial era, the success of a corporation lies more in its intellectualcapital and system capabilities than in its physical assets. The capacity to manage intellectual capital-and to convert it into useful products and services to fast becoming the critical executive skill of the age. As a result, there has been a flurry of interest in intellectual capital, creativity, innovation, and learning organization. However, the debate about how measure the intellectual capital still exist within the expert.